Effects of the chinese yuan devaluation on the Singapore economy. - Chua, Sze Ying. (2008)
This paper thus seeks to assess the impact on one of the ASEAN countries, Singapore, should the yuan devalue. With the consensus that Singapore's economy is somewhat complementary to China's, it distinguishes the former from most of ASEAN economies. A yuan devaluation might at the very least, not hurt Singapore's exports directly but the contagion effects in the region might affect Singapore indirectly after all.